Penguatan Kebersamaan Dengan Berbuka Puasa Bersama Serta Tebar Mushaf Madinah Di Panti Asuhan Aisyiyah Payakumbuh - Solihati, Septia; Hidayat, Tatang; Fairuzana, Nadhira; Salsabila, Syifa; Januarti, Putri; Hashifah, Nabilah; Putri, Dilla Hardiyana; Azzahra, Giana (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
Ramadan is a month synonymous with togetherness. Among the activities that foster togetherness is breaking the fast together. Breaking the fast together has become one of the deep traditions in our culture. In an effort to increase social awareness and share with others, we carried out a community service initiative by holding iftar activities together at Aisyiyah Payakumbuh Orphanage. This service aims to analyze the impact of breaking the fast together on the welfare of the orphanage children. The methods used are participatory observation and interviews. The results of the service showed that this breakfasting activity had a significant impact on the social welfare of children in the orphanage, both in terms of emotional and psychological. Participation in this activity increases a sense of togetherness and happiness and provides valuable social experiences for children living in orphanages.